Clinical-Epidemological Study of Cryptococcosis in Venezuela, 1994-2003 - Celina Pérez de Salazar; Yumaira Hernández; María Eugenia Guzmán; Félix Arias; Luzalba Nweihed; María Eugenia Landaeta; Rafael Borges; Carlos Madera; Arantza Roselló; María Colella; Claudia Hartung; Sofía Mata Essayag (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2009)
Cryptococcosis is an opportunistic disease of worldwide distribution. It is frequently an AIDS-defining infection. Antiretroviral treatment has reduced its occurrence. In Venezuela, the impact of this disease is unknown. The aim of this study is to describe the most relevant features of cryptococcosis in our country. Methods: 110 clinical records with a diagnosis of cryptococcosis hospitalized between 1994 and 2003 in 6 Venezuelan hospitals were analyzed. Data collected included demographic, clinical, diagnostic, therapeutic and outcome information. SPSS 10.0 software and EpiInfo 6, version 6.04 (2001) were used. Results: 110 patients with cryptococcosis were enrolled, including 17 autopsy protocols. One was 8 years old, the rest were over 15. Nineteen were female and 91 male; 91 (82.73%) had AIDS, 19 (17.27%) were HIV negative. Among the AIDS patients, average CD4+ count was < 200 cel/mm3 and viral load was > 30000 co pies/ml; 52 (57.14%) did not have other opportunistic infections or AIDS-related disease, and 39 (42.86%) had other associated conditions, such as tuberculosis (30.97%), PCP (28.21%) and toxoplasmosis (20.51%). In HIV negative patients, use of steroids (25%) was the predominant risk factor. Two patients were pregnant. 107 (57.27%) presented CNS infection; 12 (13.19%) with AIDS had cranial nerve alterations. Pulmonary disease was found in 4 (3.77%), of which one had AIDS. Cryptococcosis was an AIDS-defining infection in 61.54% of cases; 33 (30%) of the patients died. Conclusions: In most of the patients, cryptococcosis was associated with AIDS. In spite of the efficacy of antiretroviral treatment, this mycosis is still significant in Venezuela, perhaps due to late HIV infection diagnosis.